The village by the sea : an Indian family story - Desai, Anita (Melbourne : Heinemann, 1982)
Lila is thirteen and her brother Hari only twelve, yet as the eldet children of a poor Indian family they have to cope when their parents cannot support them. Hari leaves the village to find work in the teeming city of Bombay, while Lila looks after her younger sisters and sick mother. They both have different challenges to face in this absorbing of life ij a rapidly changing country.
Keywords: Families -- India -- Juvenile fiction; Brothers and sisters -- Juvenile fiction; Poverty -- Juvenile fiction